Work and leisure - Haworth, John Trevor; Veal, Anthony James (Routledge, 2004)
"Work and Leisure brings together specially commissioned chapters from international experts in a wide range of disciplines concerned with work, leisure and well-being. Each author takes stock of the current position, identifies core practical and theoretical issues and discusses possible future trends in order to provide an invaluable resource for all policy-makers, educators, employers and researchers in the field."--Jacket